The Development of Number Fishing Media to Enhance the Ability to Recognize Number Concepts in Children Aged 5–6 Years - Oktavianty, Redita Pramesti; Widayati, Sri (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study was motivated by the low ability of children aged 5–6 years to recognize the concept of numbers 1–10, as well as the limited use of engaging learning media appropriate to children’s developmental stages at TK RA Kartini Lamongan. The purpose of this research was to examine the feasibility and effectiveness of the Number Fishing media in improving the ability to recognize number concepts in children. The study employed the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product developed was Number Fishing media made of flannel fabric, consisting of a fish pond, fish numbered 1–10, magnetic fishing rods, colored dice, and fish containers. Validation was conducted by two material experts and two media experts using a Likert-scale assessment sheet. The validation results indicated that the media was highly feasible, with average scores of 95.83% from material experts and 96.88% from media experts. Effectiveness testing was carried out using pretest and posttest analyzed with the Wilcoxon test, yielding an Asymp. Sig. (2-tailed) value of 0.002 < 0.05. These findings demonstrate that the Number Fishing media is feasible, effective, interactive, and aligned with the developmental characteristics of early childhood.